SCIENTIA SACRA IN SUFISM AS WELTANSCHAUUNG CONTEMPORARY MUSLIM SPIRITUALITY - Imron Mustofa (UIN Raden Mas Said Surakarta, 2021)
This study examines the peripheral area of Sufistic reasoning, where modern humans lose their orientation and cause a psychological crisis through a fundamental philosophical assessment of the weltanschauung as the axis of Sufism spirituality in Islam, focusing on the contemporary perspective of modern society and the construct of Scientia sacra as the weltanschauung of contemporary Muslim spirituality. The study results confirm that the fundamental problem that represents the relationship between spirituality and modern society is the dualism of the ontology-epistemic framework, as a result of the split understanding between Sufism and its pseudo. The Sufis have built the concept of Scientia sacra based on the integration of theosophical reasoning, ascetic praxis, and philosophical nature. This concept is expected to present conceptual-praxis activities described as exclusive mujahadah , trendy, and introvertistic that €œcatharsis€ themselves from the worldly bustle but have communal, philosophical values closely related to the values rahmat al-khalq. The philosophical basis of this movement originated from theosophical reasoning, transformed into praxis asceticism, and developed as philosophical asceticism. These three elements come from the key statement that Sufism is an existential axis for humans, where the crisis of modern humans is the centrifugal motion of that axis. It is what causes the philosophical values in Sufistic teachings to experience turmoil, ending in a cathartic process towards Scientia sacra as the basis of knowledge, metaphysics, and esotericism.